WA VELET-DCT BASED IMAGE CODER FOR VIDEO CODING APPLICATIONS - GANI, REGINA (Universiti Teknologi Petronas, 2008)
Utilization of digital video raises important concern on storage space and transmission purpose. A video codec that compresses digital video signal has become an essential component in video application. The interest of this project is to integrate a wavelet-based compression and at the same time providing a backward compatibility to the existing architecture of MPEG-2 standard. Wavelet-DCT is an algorithm that utilizes Discrete Wavelet Transform (DWT) to compute Discrete Cosine Transform (DCT) coefficients. The algorithm allows truncation of intermediate coefficient through DWT. This process is also known as thresholding. The Wavelet-DCT algorithm is integrated into a simulation of intra-frame coder in compliance with MPEG-2 standard. To enhance the system performance, threshold level selection is done via histogram energy analysis and selection of best wavelet type through statistical study. The simulation was developed using SIMULINK and MATLAB. WaveletDCT based intra-frame coder was simulated by employing two different approaches. Different types of multimedia source (image and video) were tested on the simulation. The result from both approaches for images shows marginal improvement at higher compression ratio. On the other hand, when it was tested on video, which consists of different types of images, both approaches does not show a reasonable improvement at various level of compression ratio. The argument on why wavelet-DCT based intra-frame coder does not perform better arises from the objective's restriction that attempts to cater the backward compatibility. Some recommended areas to be delved for future work on video compression are distributed video coding, ridgelet transform and dual-tree complex wavelet transform.